Identitas Etnis Arab Dan China Di Surabaya - Sentit Rustiani (LPPM Politeknik Pratama, 2023)
Multicultural means consisting of various ethnicities, religions, races and cultures, one of the things that the Indonesian people are grateful for because they can understand the differences between various styles and societies. One of the tribes that is of concern is the Arab and Chinese tribes, where these two tribes have many differences, starting from cultural habits and so on. This is interesting because the differences between the two are whether they are the beginning of division or the beginning of unity. Including in Suabaya itself there are two villages representing Arab and Chinese tribes. The Arab ethnic group found in the city of Surabaya or more in the Sunan Ampel area is mostly no longer native to the Arab ethnic group, but rather a mixture of Arab and Javanese ethnicities, but even so, the biological characteristics of the Arab ethnic group continue to be inherited by people who are of ethnic descent. the Arabic. so that we can distinguish whether they are of Arab ethnic descent or not, one of them is through their physical appearance, where women of Arab ethnic origin have sharp noses and white skin and they also always decorate their faces with black eyeshadow wherever they are, whereas for women Men of Arab ethnicity also have sharp noses and long or bushy beards. Meanwhile, the Chinese tribe stands with a characteristic physical form such as slanted eyes and another cultural tradition in Chinatown village, namely the moon cake celebration. This moon cake is shaped like the moon, namely round and contains various kinds of fillings such as nuts. This makes tolerance the basis for caring for differences, such as different livelihoods and different habits. This must be the framework for caring for unity. Their characteristics must be well cared for but also not abandon their mutual respect for each other. This is the essence of Indonesia's goal in the 1945 Constitution, namely to become a sovereign, independent, united, prosperous and prosperous country.